Gastos por COVID-19 en la región Loreto y su relación con el gasto por COVID-19 a nivel nacional periodo 2020-2022 - Flores Reategui, Aldair Antonio (2024)
The challenge of public management in the face of the COVID-19 pandemic was to address an unprecedented crisis, which required rapid and effective responses on multiple fronts, which represented significant challenges in public health management, resource allocation, communication. and education to the population, the mitigation of the socioeconomic impact and international coordination, the general objective of this study is to determine the relationship between the expenses due to Covid 19 at the level of the Loreto region and the expenses due to Covid-19 at the national level, developing a quantitative observational methodology and a correlational non-experimental design, taking as a sample the budgetary financial data corresponding to the period 2020 2022, the study identified that during 2020-2022, a statistically significant relationship was found between COVID-19 expenses in Loreto and a national level, both in the source of financing and in the generic of expenditure. A negative and similar trend was observed in spending between Loreto and the national level, in addition Lima, Lambayeque and Cajamarca received more funds, while Moquegua, Madre de Dios and Tacna less concluding that no statistically significant relationship was found between the spending of the Loreto region and national spending during the COVID-19 pandemic, which could be attributed to the prioritization of spending that was based on a variety of factors specific to each region.